Using Virtual Reality Exposure Therapy to Enhance Treatment of Anxiety Disorders: Identifying Areas of Clinical Adoption and Potential Obstacles - Boeldt, Debra; McMahon, Elizabeth; McFaul, Mimi; Greenleaf, Walter (Frontiers in Psychiatry, 2019)
Despite strong evidence of effectiveness, exposure therapy is an underutilized treatment for anxiety disorders at a time when effective treatment for anxiety is greatly needed. The significant worldwide prevalence and negative impact of anxiety are documented and highlight the importance of increasing therapist and patient use of effective treatment. Obstacles to the use of exposure therapy are explored and steps to lessen these obstacles are proposed. In particular, virtual reality (VR) technology is discussed as a way to increase the availability of exposure therapy. Incorporating virtual reality (VR) in therapy can increase the ease, acceptability, and effectiveness of treatment for anxiety. VR exposure therapy (VRET) permits individualized, gradual, controlled, immersive exposure that is easy for therapists to implement and often more acceptable to patients than in vivo or imaginal exposure. VR is presented as a scalable tool that can augment access to and effectiveness of exposure therapy thus improving treatment of anxiety disorders. VR also has the potential to help with assessment and with therapist training standardization. The authors advocate for providing continuing education in VRET to practicing clinicians and including training in exposure therapy and VRET in training programs. Ongoing development of VR applications for clinical use is encouraged, especially when developed in collaboration with software developers, clinical users, therapists who are experienced in VRET, and researchers.